Modelagem matemática de epidemias: uma abordagem com modelos compartimentais. - OLIVEIRA JÚNIOR, Valdir de (2021)
Mathematical modeling consists of the representation of a phenomenon or description of the behavior of a system through mathematical language, for example, using models that can be represented by differential equations and mathematical statistics. In epidemiology it is a crucial tool to characterize the behavior of infectious diseases over time, as well as in decision making by organizations that deal with Public Health. In this work, we propose the use of compartmental models to determine indicators related to the spread of diseases. An application with artificial parameters of COVID-19 is carried out to illustrate the methodology in the context of High School. GeoGebra is used to build the graphical representation of the numerical solutions of the compartmental models SIR and SIS. An extensive bibliographic research was developed to study the theme and emphasize its relevance.